Dental age estimation of Malaysian children: a comparison of two-dimensional versus three-dimensional imaging analyses of the developing root apices - Muhammad Khan Asif; Norliza Ibrahim; Iqra Muhammad Khan; Shah Salman Khan; Phrabhakaran Nambiar (Taylor & Francis Group, 2022)
Aim This study compared the effectiveness of the three-dimensional (3D) cone beam computed tomography (CBCT) method of age estimation developed by Asif et al. with two-dimensional Cameriere's method. Subjects and methods CBCT images belonging to 129 Malaysian Chinese and Malay ethnic groups aged 7-14 years were investigated and analysed. Results The results indicated a strong correlation between chronological age and the predictor variables for both Cameriere's (r = 0.984) and Asif's (r = 0.988) methods of age estimation. Fisher Z test analysis indicated no statistically significant difference in the correlation values between the two methods. Mean absolute error (MAE) value of 0.613 was observed for Cameriere's and 0.290 was observed for Asif's method. Conclusions The results indicated that the methods of age estimation from both Asif et al. and Cameriere et al. are applicable on Malaysian children. However, Asif et al.'s 3D CBCT method of age estimation resulted in greater accuracy and reliability in estimating chronological age.